ANALISIS PENGARUH INOVASI DAN KEUNGGULAN BERSAING SEBAGAI VARIABEL INTERVENING ORIENTASI PASAR DAN PENGGUNAAN ERP TERHADAP KINERJA PEMASARAN (Studi Pada Usaha Mikro Kecil dan Menengah di Kota Semarang) - Kurniawan, Danang; Mudiantono, Mudiantono (Diponegoro Journal of Management, 2018)
Business competition in the current era of globalization requires companies to have a strategy to win the competition. Strategic management has an important role for the survival of the company. The existence of such competition is also felt by small businesses such as Micro, Small and Medium Enterprises (MSMEs). The increase in the number of MSME units in Central Java was not followed by an increase in average turnover Micro, Small and Medium Enterprises. This study aims to analyze the effect of innovation and competitive advantage as an intervening variable on market orientation and implementation ERP on marketing performance.The population in this study were Micro, Small and Medium Enterprises owners, where respondents were owners of Micro, Small and Medium Enterprises in the city of Semarang. The number of samples used was 128 respondents. The method of data collection is done through a questionnaire method. This study uses Structural Equation Modeling (SEM) analysis techniques using the AMOS 24 analysis tool.The results of this study indicate that the market orientation is a positive effect on innovation, implementation ERP has a positive effect on innovation, the market orientation is a positive effect on competitive advantage, implementation ERP has a positive effect on competitive advantage, innovation has a positive effect on competitive advantage, market orientation has a positive effect on marketing performance, innovation has a positive effect on marketing performance and competitive advantage bar has a negative and insignificant effect on marketing performance.